Watermarking Study on The Vector Map - Hartanto Tantriawan; Rinaldi Munir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
In addition to being employed in a variety of military and security applications, GIS vector maps are frequently used in social, environmental, and economic applications like navigation, business planning, infrastructure & utility allocation, and disaster management. Given the high value of this map, copyright protection is implemented in the watermarking as a required safeguard against unauthorized modification and exchange of GIS vector maps. Watermarking is inserting information (watermark) stating ownership of multimedia data. This paper discusses several approaches that can be used to watermark vector maps, including using the space-domain algorithm and transform-domain algorithm. Second The watermarking algorithm was developed with the following quality metrics: fidelity, robustness, capacity, complexity, and security. The challenge in this study is that the higher the capacity, the lower the fidelity value. Low fidelity causes map properties to be lost, making the map unusable. These two things need to be balanced.